PENGARUH KOMPENSASI FINANSIAL DAN GAYA KEPEMIMPINAN TERHADAP MOTIVASI DAN KINERJA KARYAWAN (STUDI PADA BANK JATIM CABANG BOJONEGORO) - Ardiansyah, Naufal; Andriyani, Andriyani (Diponegoro Journal of Management, 2019)
The measure of success of a field of staffing is performance. This is because the field itself and employees need feedback on their efforts, so the performance of each employee needs to be assessed. Many factors can influence employee performance, such as financial compensation, leadership style and motivation. The purpose of this study was to analyze the effect of financial compensation and leadership style on work motivation, the effect of work motivation on employee performance and the influence of leadership style on employee performance.The study population was employees of Bank Jatim, Bojonegoro Branch, Jl. Mastrip No. 70, Bojonegoro, East Java, totaling 129 employees. Samples taken 100 employees. The type of data used is primary data. Methods for collecting data are questionnaires. The analysis technique used is path analysis, with previously tested by instrument test and classic assumption test.The results showed that: Financial compensation has a significant effect on work motivation. Leadership style has a significant effect on work motivation. Motivation has a significant effect on employee performance. Leadership style has a significant effect on employee performance